The Level Of Use And Acceptance Towards Online Learning In Covid-19 Pandemic (Case Study Of College Students In Pontianak) - Melya Yosita; Aisyah Aisyah; Windi Pratiwi (Jurnal Ilmiah Manajemen dan Bisnis, 2021)
This research to determine the perceptions of college students in Pontianak City on the level of adoption, use and acceptance of online learning during the COVID-19 pandemic. This research is a descriptive quantitative using non-probability sampling with purposive sampling and quota sampling techniques. The sample of this research is college students in Pontianak City with 180 respondents. The data analysis technique used is descriptive analysis with a focus on the elements of the average. The results showed the respondents 'responses regarding Attitude, Affect and Motivation towards online learning when the Covid-19 epidemic obtained the highest index value of 153, included in the high category, respondents' responses regarding Perceived Behavioral Control obtained an index value of 145.5 also included in the high category. Meanwhile, the respondents' responses regarding Perceived Behavioral Control have an index value of 120.5 in the medium category. The conclusion of research is that college students in Pontianak City prefer face-to-face learning activities compared to online learning. The ease of use of the online education platform and the acquisition of higher scores were also felt by students when participating in online learning. The majority of university students in Pontianak are still not satisfied with online learning